THE EFFECT OF ABRASIVE GRAIN SHAPES ON QUALITY OF FERRITE MAGNETS GRINDING PROCESS - Bayu Rahmat Saputro; amin suhadi (Majalah Ilmiah Pengkajian Industri, 2020)
Abstract A research was conducted on the grinding process of ferrite magnet with Strontium ferrite type (SrO.6 (Fe2O3)) using electroplated single layer grinding wheels. Many cracks have been found on work pieces during this work, which is coming from grinding processes. Research is conducted starting from chemical composition test and the effect of the shape and size of the abrasive grain of grinding wheels to the quality of grinding process results by measuring crack ratio of the work piece. In this experiment, 3 (three) model design of grinding wheels with three different size and shape of abrasive grains are made. All of processing parameters are set at the same value as ordinary process. The experimental results shown that 3rd model have the best results from the outputs number and also the lowest reject crack ratio compared to 1st and 2nd models. This is because the 3rd model has blocky shape which its distribution structure is denser and more uniform compared to the irregular shape, so that continuous grinding on hard and brittle work pieces is more stable and suitable